MON-LB090 Red-Hipopara, Real Life Experience in 322 Patients with Hypoparathyroidism in Argentina - Zanchetta, Maria (J Endocr Soc, 2019)
Hypoparathyroidism (HPT) is a rare disorder characterized by hypocalcemia and absent or deficient PTH. Few data are available on the natural history and correct management of this disease. Aim: Describe clinical characteristics, treatment, and complications in a group of patients with hypoparathyroidism from 6 referral centers for endocrinological diseases. Secondary, describe how many patients reached guidelines recommendations for rhPTH (1-84) treatment (Brandi ML. JCEM. 2016). M & M: In this retrospective study patients with a diagnosis of HPT of ≥6 months were eligible for inclusion. Patients with pseudohypoparathyroidism were excluded. Demographics, etiology, management, hospitalizations, clinical manifestations and biochemical and DXA values were collected.Results:322 HPT patients were included; mean age was 55.2 ± 16.8 years, 85,7% were women. Mean ageat diagnosis was 43.8 ± 16.8 years and mean follow up time was 4.9 ± 5.1 years. Regarding etiology 90%were post-surgical (50.3% for thyroid cancer, 41% for multinodular goiter, 2.7% primary hyperparathyroidism;3.4% secondary hyperparathyroidism and 2.3% cervical cancer). Non-surgical etiology included: 5 DiGeorge Syndrome, 9 autoimmune and 16 idiopathic. Non-surgical patients were significantly younger (45 ± 19.5 vs.56.3 ± 16.1 years; p<0.01) and were younger at diagnosis (45.1 ± 15.9 vs. 31.4 ± 20.5 years;p<0.01).Treatment regimens were determined by the patients’ physician, per usual clinical practice, and most patients were receiving calcium supplementation (mean daily dose:2019 ± 1426 mg), vitamin D ( mean weekly dose 34.368 ± 55.278 UI) and calcitriol ( mean daily dose: 0.498 ± 0.279 mcg). 13 patients were receiving teriparatide ( 1-34 human parathyroid hormone). 25.7% had a history of hypocalcemia requiring hospitalization, 4.6% had fragility fracture history (wrist, hip, humerus, vertebra or tibia) and 4.3% has a history of seizures. Only 41.9% had a renal ultrasound done and 15.5 % had positive findings ( kidney stones and nephrocalcinosis). 54% had 24-hour urine calcium excretion measured and almost half of them had hypercalciuria confirmed (56.3%). Only 18,3% patients had central nervous system imaging performed,and 38.9% had basal ganglia calcification. Finally, 38.8% met criteria to rhPTH (1-84) treatment according to the guideline; most of them because their daily oral calcium requirements exceeded 2.5 g of calcium. Conclusion: Although these patients were followed by experienced physicians, clinical management and monitoring was heterogeneous and probably insufficient to assess all the potential complications of this chronic disease. Being aware of this situation is the first step to improve our medical management of HPT in the future Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.